Pyrrolopyrrole-Based Aza-BODIPY Small Molecules for Organic Field-Effect Transistors - Zhang, Daohai; Liang, Dongxu; Gu, Liang; Zhang, Haichang (Frontiers in Chemistry, 2022)
Diketopyrrolopyrrole (DPP), due to its good planarity, π-conjugate structure, thermal stability, and structural modifiability, has received much attention from the scientific community as an excellent semiconductor material for its applications in the field of optoelectronics, such as organic solar cells, organic photovoltaics, and organic field effect transistors. In this study, a new small molecule, pyrrolopyrrole aza-BODIPY (PPAB), based on the thiophene-substituted DPP structure was developed using the Schiff-base formation reaction of DPP and heteroaromatic amines. Absorption spectroscopy, electrochemistry, X-ray diffraction, molecular theoretical simulation calculation were performed, and organic field-effect transistor properties based on PPAB were investigated. It was found that PPAB exhibits a broad absorption range in the visible and near-infrared regions, which is attributed to its long-range conjugate structure. In addition, it is worth noting that PPAB has multiple F atoms resulting in the low LUMO level, which is conducive to the injection and transportation of charge carriers between the semiconductor layer and the electrode. Meanwhile, its hole carrier mobility is up to 1.3 × 10−3 cm2 V−1 s−1 due to its large conjugate structure, good intramolecular charge transfer effect, and high degree of coplanarity. In this study, a new chromophore with electron-deficient ability for designing high-performance semiconductors was successfully synthesized.